Cultivating Teacher Resilience International Approaches, Applications and Impact - Mansfield, Caroline F.; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2020)
This open access book follows the development of the Building Resilience in Teacher Education (BRiTE) project across Australia and internationally. Drawing on the success of this project and the related research collaborations that have since emerged, it highlights the importance of cultivating resilience at various stages of teachers' careers. Divided into three sections, the book includes conceptual, empirical and applied chapters, designed to introduce readers to the field of research, provide empirical evidence and showcase innovative applications. The respective chapters illustrate the ways in which teacher resilience can be enhanced in a variety of contexts, and address specific learning activities, case studies, resources and strategies, student feedback and applied outcomes. They also consider future directions including cross-cultural applications and the use of technologies such as augmented reality. The book will appeal to researchers, teacher educators and teachers, as well as those interested in supporting the cultivation and ongoing development of professional resilience for pre-service and practicing teachers.
Section 1 Introduction -- 1 Why teacher resilience? -- 2 Understanding and examining teacher resilience from multiple perspectives -- 3 A BRiTE journey -- Section 2 Implementation and Applications -- 4 Staying BRiTE: An introduction -- 5 Connecting, embedding and developing BRiTE across multiple levels -- 6 Thinking dispositions for teaching: Enabling and supporting resilience in context -- 7 Implementing BRiTE in Initial Teacher Education Programs: through the eyes of the teacher educators -- 8 Doing it resiliently: Using arts-based approaches to embed resilience in professional experience learning -- 9 Building resilience for Early Years teachers -- 10 BRiTE mind: An online module to support mindful teacher resilience -- Section 3 Interventions and Impact -- 11 Building Resilience: Using BRiTE with beginning teachers in the US -- 12 Positive education: A professional learning programme to foster teacher's resilience and well-being -- 13 The professional assessment and development induction program: Application of the BRiTE project to the Spanish context -- 14 Practical applications for building teacher wellbeing in education -- 15 Understanding teacher wellbeing through job demands-resources theory -- Section 4 Future Directions -- 16 BRiTE-AR ways to prepare preservice teachers: Augmented reality addressing conflict and stress -- 17 Staying BRiTE in the Dutch teacher education context -- 18 Navigating changing times: Exploring teacher educator experiences of resilience -- 19 Looking back and moving forward.
Keywords: Teaching; Professional education; Vocational education; 9; Education and sociology; Positive psychology; Teaching and Teacher Education; Professional & Vocational Education; Sociology of Education; Positive Psychology